ANALISIS PAJAK RESTORAN PROVINSI DKI JAKARTA DI ERA DIGITAL DALAM METODE SWOT - Devi Siswati; Inayati Inayati (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2022)
This study attempts to analyze the restaurant tax to increase Regional Original Income (PAD) in DKI Jakarta Province by describing the potential and obstacles amid the opportunities and challenges in the digital era. The results of the analysis of this study aim to explore the expansion of the restaurant tax base by utilizing technology to increase digital transactions. The method in this study uses the SWOT analysis methods. The data was obtained from the official website of the Regional Revenue Agency of DKI Jakarta Province from 2019 to 2020 by using documentation study data. This study concludes that the regional tax authority of DKI Jakarta Province is needed to oversee digital transactions as an expansion of the restaurant tax base regulated by local laws and regulations in the digital by utilizing technology to increase digital transactions amid the Covid-19 pandemic. Thus, collaboration with other institutions will give success of modernizing the restaurant tax administration system can be an opportunity to expand the tax base against challenges in the digital era that have a positive impact on local tax revenues and positive regional fiscal quality the DKI Jakarta Provincial Government in implementing regional autonomy.